2022
DOI: 10.1080/14786419.2022.2032050
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of hispidulin

Abstract: There are conflicting reports on the antioxidant activity of hispidulin. Antioxidant activity of hispidulin was evaluated using assays of ABTS • reduction, ferric ion reducing antioxidant power (FRAP) assay, DPPH reduction assay, and protection of erythrocyte membranes against lipid peroxidation and protein thiol oxidation. ABTS • reduction assay pointed to the involvement of all three phenol groups of hispidulin in ABTS • reduction. The reactivity of hispidulin in the FRAP assay and DPPH reduction assay was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Among the specialized metabolites identified in our study, particularly 1,5-dicaffeoylquinic acid has been related to a strong antioxidant activity [ 28 ]. Moreover, out of the flavonols detected, luteolin has been previously reported for its antioxidant capacity [ 29 ], while hispidulin showed contrasting results, being not active in cell-free systems but effective in the protection against erythrocyte membrane lipid peroxidation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the specialized metabolites identified in our study, particularly 1,5-dicaffeoylquinic acid has been related to a strong antioxidant activity [ 28 ]. Moreover, out of the flavonols detected, luteolin has been previously reported for its antioxidant capacity [ 29 ], while hispidulin showed contrasting results, being not active in cell-free systems but effective in the protection against erythrocyte membrane lipid peroxidation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that LPS-injected animals display marked oxidative stress and tubular cell apoptosis in the kidneys [ 46 ]. Hispidulin has been known to possess an antioxidant property [ 48 ]. In this study, LPS injection induced an increase in lipid and DNA oxidation products.…”
Section: Discussionmentioning
confidence: 99%
“…ABTS • reacts with many substances, its reactivity being higher than that of DPPH and Fe 3+ in the FRAP assay. For example, we found that the reactivity of hispidulin with ABTS • was 2.82 mol TE/mol hispidulin, while its reactivity with DPPH and Fe 3+ (FRAP assay) was negligible (0.019 and 0.09 mol TE/mol hispidulin, respectively) [43]. Similarly, capsaicin showed a reactivity with ABTS • of 0.74 (Table 1), a reactivity in the FRAP assay of 1.103 mol TE/mol, and only 0.079 mol TE/mol with DPPH (submitted).…”
Section: Alternative Parameters To Measure Antioxidant Activitymentioning
confidence: 97%